Articulação entre saúde mental infanto-juvenil e atenção básica em Natal-RN: limites e possibilidades - Silva, Paola da Costa (2014)
In the case of Brazilian Psychiatric Reformation, mental health juvenile reveals itself as a great challenge, with major gaps in terms of needs, services and actions on mental illness in children and adolescents. This research is a qualitative study of descriptive and exploratory, having to analyze the actions and practices of mental health juvenile articulated between the Psychosocial Care Center juvenile (Caps i) and the basic care in Natal-RN, and specific, identify the limits and possibilities for an important precedent of the care network. After submission to the Research Ethics Committee (CEP) of the University Hospital Onofre Lopes (HUOL) of the Federal University of Rio Grande do Norte (UFRN) obtained approval contained in opinion number 777.067 / 2014. For the data collection, it was initially carried out a documentary research in the Municipal Health Department of Christmas about the phenomenon under study, and subsequently, applied semi-structured interviews with the subjects of the research, which were workers Caps i of Natal-RN. The analysis was woven as the thematic analysis technique, understood within the method of content analysis. The results and discussions were organized by categories and subcategories, namely: CATEGORY 1: Limits and weaknesses in the linkage between the Caps i and basic care, with the subcategories: 1.1 Lack of specialized services and devices articulators in network, 1.2 The diversity of situations in the demand juvenile assisted; CATEGORY 2: possibilities for an effective network, with the subcategory: 2.1 Intersectoral collaboration as a strategy for solving attention. The analysis revealed that the integration and coordination of mental health services juvenile and primary care in the city of Natal-RN, has incipient initiatives and/or inadequate for the resolvability intersectoral, where the devices of attention to health involved cannot establish bonds effective and long-lasting in the perspective of co-responsibility and sharing of care. On the other hand, it appears that the existing shares and practiced, configure an exercise in approximation to the dialog between mental health juvenile and basic care. It is highlighted that the shared care and the establishment of intersectoral collaboration within and outside of the health sector is possibility of facilitating the necessary dialog between the services and professionals involved, thus, enabling a better prospect of resolvability of the Network of Psychosocial Care for the youth in reality being investigated.